Global Perspectives of COVID-19 Pandemic on Health, Education, and Role of Media - Pachauri, Saroj; Pachauri, Ash (Springer Nature, 2023)
This open access book discusses the impact of the COVID-19 pandemic on various aspects of life on a global scale. It analyzes the challenges in the healthcare system during the second wave of COVID-19, such as overstressed human resources in tertiary facilities, lack of trained healthcare workers, and inadequate infrastructure at secondary-level facilities. The book shows that there has been more disruption in low- and middle-income countries than in high-income countries. It presents how the pandemic drove economies into recession and offers a roadmap to advance equality of access to and sustainability of resources. It studies the impact of prolonged lockdowns, which resulted in emotional and mental unrest. It provides a global perspective on the role of the media, including social media, during the pandemic. The authors discuss the unprecedented rise in suicides and the impact of the pandemic on vulnerable groups, such as asylum seekers and adolescents. In addition, contributing authors cover country experiences with COVID-19 in the UK, Taiwan, Ethiopia, Iran, India, and Brazil. The book's multidisciplinary approach makes it an interesting read for academics, policymakers, program implementers, and researchers in sociology, media studies, and medical experts.